Zur Taxonomie und Verbreitung der Gattung Pseudopsis Newman, 1834 (Coleoptera, Staphylinidae, Pseudopsinae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1992)
Six new species of Pseudopsis are described and their aedeagi illustrated: cyprea from Cyprus, galileensis from Israel, atratula, torta, and acuta from the Himalayas, and campbelli from Ecuador. They are part of the sulcata complex which is represented in the Palearctic region by 13 species now. A list of the Palearctic species is given and a key is provided. Nomenclatural Acts acuta Zerche, 1992 (Pseudopsis), spec. n. atratula Zerche, 1992 (Pseudopsis), spec. n. campbelli Zerche, 1992 (Pseudopsis), spec. n. cypria Zerche, 1992 (Pseudopsis), spec. n. galileensis Zerche, 1992 (Pseudopsis), spec. n. torta Zerche, 1992 (Pseudopsis), spec. n.